Utilization of Artificial Intelligence in Modern Education - Marisa, Marisa; Pertiwi, Septa; Wahyuni, Sri (Indonesian Journal Publisher, 2025)
The sophistication of information technology has had a major influence on various aspects of human life, including in the field of education. One of the prominent innovations is artificial intelligence (AI), which is now widely applied to support the learning process at various levels, including universities. This article discusses the use of AI technology in education, with a focus on its contribution to improving the quality of learning, administrative effectiveness, and providing a more personal and adaptive learning experience for students. This study uses a literature study method with a descriptive qualitative approach. The results of the study show that AI has been utilized through various platforms such as ChatGPT, Perplexity, and Gemini, which help students find references, complete assignments, and understand lecture materials. However, the use of AI also poses a number of challenges, such as dependency, plagiarism, decreased social interaction, and ethical and privacy issues. Therefore, the use of AI in education needs to be directed wisely so that this technology truly plays a positive role in supporting the teaching and learning process.